2017
DOI: 10.1002/wsb.754
|View full text |Cite
|
Sign up to set email alerts
|

Hunter cooperation with requests to avoid a visibly marked ungulate

Abstract: Studies utilizing radio tags to examine animal space use are widespread and often require the survival of marked animals over the entirety of a specified study period to answer movement-related questions. When studying the space use of game species, tactics such as applying visible markings to research animals and communicating with hunters may be needed to mitigate unwanted losses due to hunter harvest. Information regarding the effectiveness of visible markings and communication efforts in reducing harvest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…Satellite and GPS‐tags are increasingly used in conservation and management‐based projects to monitor the well‐being of individuals of threatened species (e.g., individuals released during reintroductions), to assess their mortality threats, to uncover illegal activities that may be hidden by perpetrators and thus pass under‐reported or to detect cryptic sources of mortality concentrated in remote areas of difficult access or under‐reported because politically conflictual (e.g., deaths of threatened species at wind energy facilities) (reviews in Cooke, ; Kays et al., ). In addition, these tagging devices are used to evaluate specific procedures of management or research (e.g., angling methods, hunter cooperation with legal prescriptions, predator removal, techniques of tag attachments: Bengsen, ; Donaldson, Arlinghaus, Hanson, & Cooke, ; Sexson, Mulcahy, Spriggs, & Yers, ; Wiskirchen, Jacobsen, Sullivan, & Ditchkoff, ). In all these contexts, improved precision in proper identification of remotely sensed casualties would yield marked advances in management planning, implementation, and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Satellite and GPS‐tags are increasingly used in conservation and management‐based projects to monitor the well‐being of individuals of threatened species (e.g., individuals released during reintroductions), to assess their mortality threats, to uncover illegal activities that may be hidden by perpetrators and thus pass under‐reported or to detect cryptic sources of mortality concentrated in remote areas of difficult access or under‐reported because politically conflictual (e.g., deaths of threatened species at wind energy facilities) (reviews in Cooke, ; Kays et al., ). In addition, these tagging devices are used to evaluate specific procedures of management or research (e.g., angling methods, hunter cooperation with legal prescriptions, predator removal, techniques of tag attachments: Bengsen, ; Donaldson, Arlinghaus, Hanson, & Cooke, ; Sexson, Mulcahy, Spriggs, & Yers, ; Wiskirchen, Jacobsen, Sullivan, & Ditchkoff, ). In all these contexts, improved precision in proper identification of remotely sensed casualties would yield marked advances in management planning, implementation, and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that telemetry studies provide unbiased survival estimates for white‐tailed deer and the presence of VHF collars does not influence hunter harvest selection (Buderman et al , Wiskirchen et al ). We informed landowners and hunters on and adjacent to private properties where we captured deer about the possibility of encountering collared deer and encouraged hunters not to let the presence of the collar influence their harvest decision.…”
Section: Methodsmentioning
confidence: 99%
“…The GPS collars were fluorescent orange in color and ear tags were bright yellow to aid hunters in identification of GPS-collared deer. We asked hunters on all study areas not to harvest GPS-collared deer [ 63 ]. Once collaring was complete, we reverse-immobilized deer via intramuscular injection of the antagonist Tolazine (100mg/ml tolazoline hydrochloride administered at 2.0 mg/kg, Lloyd Laboratories).…”
Section: Methodsmentioning
confidence: 99%